“A Great Soul Reincarnated among Gentiles:” The Attitude of Rabbi Avraham Yitzhak Hakohen Kook and Rav Tsvi Yehudah Hakohen Kook to Nietzsche - Shtamler, Hagay (The review of rabbinic Judaism, 2023)
This essay describes the attitude of Rabbi Abraham Isaac Hakohen Kook (1865–1935) as well as that of his son, Rabbi Zvi Yehudah Hakohen Kook (1891–1982), to Friedrich Wilhelm Nietzsche (1844–1900) and his philosophy. It shows that the father read Nietzsche differently from the son. The father criticizes Nietzsche profusely, while the son often mentions him appreciatively and even said that he was a great soul that reincarnated among the gentiles. The essays suggests that their dissimilar approaches resulted from the different intellectual challenges each faced due to the different cultural periods in which they lived.